32.7k views
1 vote
X = 4y + 3, 2x + y = -3
System of Equations

1 Answer

5 votes

Answer:

(- 1, - 1 )

Explanation:

Given the 2 equations

x = 4y + 3 → (1)

2x + y = - 3 → (2)

Substitute x = 4y + 3 into (2)

2(4y + 3) + y = - 3 ← distribute parenthesis and simplify left side

8y + 6 + y = - 3

9y + 6 = - 3 ( subtract 6 from both sides )

9y = - 9 ( divide both sides by 9 )

y = - 1

Substitute y = - 1 into (1) for corresponding value of x

x = 4(- 1) + 3 = - 4 + 3 = - 1

solution is (- 1, - 1 )

User Arinjit
by
4.3k points